X-ray Diffraction Peak Profile for Determination of Microstructural Properties of Hematite (Fe2O3) - Ilmi, Moh Mualliful; Nurdini, Nadya; Maryanti, Evi; Setiawan, Pindi; Ismunandar, Ismunandar (Journal of Research and Development on Nanotechnology, 2021)
Hematite (a-Fe2O3) nanoparticles have been synthesized by chemical co-precipitation method at room temperature and characterized by X-ray diffraction (XRD) study. The XRD pattern indicates that synthesis hematite NPs exhibited pure phase with hexagonal wurtzite geometry. Crystallite size calculated using Scherrer formula has been compared with that estimated by Several Williamson-Hall methods i.e., uniform deformation model (UDM), uniform stress deformation model (USDM) and uniform deformation energy density model (UDEDM), and also by size-strain plot (SSP) method. The lattice strain has also been calculated. The morphology of the product have been characterized by Transmission electron microscopy (TEM). Through the TEM image, the grain size distribution of the hematite nanoparticles was obtained using Image-J software. Among all the methods, SSP method shows highest linear fit with experiment data.